PENGEMBANGAN SISTEM INFORMASI MANAJEMEN PARIWISATA BERBASIS WEB - Titi Sriwahyuni; Oktoria Oktoria; Ika Parma Dewi (Universitas Negeri Padang, 2019)
Tourism is a field that is currently developing. This is supported by the wealth of Indonesia's natural potential which is known as the emerald equator. But not all tourism area information can be obtained easily. Because so far tourism promotion still uses pamphlets, leaflets or brochures. This can be overcome by developing a system that can be accessed by everyone by utilizing Information Technology. The aim of the research is to produce a Web-based tourism management information system. System development method is a prototyping model by utilizing PHP programming and MySQL database. The results of the system development resulted in a Web-based tourism management information system with a case study in the South Coastal Region of West Sumatra Province that could help tourism agencies in developing regional tourism.